Pengaruh Indikator Kesejahteraan Rakyat terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Verlina Agustine; Fadiah Izzah Ajrina; Ilham Firman Ashari; Azwarman Azwarman (Universitas Batanghari Jambi, 2023)
Economic growth is one indicator of successful development. An important indicator for knowing the economic conditions in a region in a certain period can be shown by the Gross Regional Domestic Product (GDP) data. An economy is said to experience a change in its development if the level of economic activity is higher than that achieved in the past. Thus, the higher the economic growth, the higher the social welfare. Jambi Province is one of the provinces on Sumatra Island whose economic growth is still below national economic growth, so it is necessary to develop a strategy to overcome this problem. This study uses multiple regression analysis to determine the variables of the people's welfare indicators that influence GRDP in Jambi Province by district/city. From the analysis results, two variables affect the GRDP value in Jambi Province: the percentage of houses with proper sanitation and IPM. It can be concluded, if the Provincial Government of Jambi wants to increase GRDP, then development can be directed at improving proper sanitation services in community housing environments and increasing the IPM of Jambi Province.